2017
DOI: 10.1093/rb/rbx015
|View full text |Cite
|
Sign up to set email alerts
|

Mineralized collagen artificial bone repair material products used for fusing the podarthral joints with internal fixation—a case report

Abstract: In this study, we reported a case with collapse and subluxation of metatarsal-cuneiform joint, navicular-cuneiform joint with subluxed the right first metatarsophalangeal joint. The injured medial column was internally fixed with compression arthrodesis. The fusion site was firmed up with BonGold® Bone Sponge and Bone Putty. The prognosis of fused navicular-cuneiform joint and metatarsal-cuneiform joint were examined by X-ray shortly after surgical operation and followed up 2, 4, 6, 9 and 13 weeks after the su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 16 publications
0
10
0
Order By: Relevance
“…Ghate et al. [ 78 ] employed Bongold™ for the first time and it had a critical influence on podarthral joint defect repair ( Fig. 8 ).…”
Section: Commercially Available Bioabsorbable Bone Substitute Materialsmentioning
confidence: 99%
“…Ghate et al. [ 78 ] employed Bongold™ for the first time and it had a critical influence on podarthral joint defect repair ( Fig. 8 ).…”
Section: Commercially Available Bioabsorbable Bone Substitute Materialsmentioning
confidence: 99%
“…Many in vitro animal studies also have been verified the biocompatibility, biodegradability and osteoconductive potency of MC [ 38 , 39 ]. For example, Ghate et al demonstrated that MC applied for the patient with collapse and subluxation of metatarsal-cuneiform joint acted as an excellent alternative to autograft in fusing the podarthral joints with internal fixation [ 40 ]. Liu et al also investigated the effect of MC on the rabbit rib defect, and reported that the MC group showed a higher bone remodeling activity in comparison with blank control group [ 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…Peng et al observed the effect of MC for the treatment of senile proximal humeral osteoporotic fractures, proving that it can accelerate healing of senile proximal humeral fracture, improve the therapeutic effect and reduce the complications 30 . Ghate et al demonstrated that MC applied for the patient with collapse and subluxation of metatarsal-cuneiform joint acted as an excellent alternative to autograft in fusing the podarthral joints with internal xation 34 . Liu et al also investigated the effect of MC on the rabbit rib defect, and reported that the MC group showed a higher bone remodeling activity in comparison with blank control group 35 .…”
Section: Discussionmentioning
confidence: 99%